The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app10196881
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Numerical Simulation Models for the Prediction of Acoustic Behavior of Giant Reeds Shredded

Abstract: Giant reeds represent a natural fiber widely available in some areas of the world. Its use can be particularly useful as the uncontrolled growth of giant reeds can be a problem because large areas are invaded by them and the crops are damaged. In this study, two models of numerical simulation of the acoustic behavior of giant reeds were put in comparison: the Hamet model and a model based on artificial neural networks. First, the characteristics of the reeds were examined and the procedures for the preparation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…However, profiling a concave in the plate and directing it with its front face to the sound wave causes an increase in sound absorption, Figure 11. Taking into account the published results of previous studies [21], which indicated the validity of the use of convexity on the back of the composite plate, which was confirmed in Figure 12, the absorption of the plate with concavity was measured comparatively. The results showed that convexity on the plate is more advantageous than concavity, Figures 11 and 12.…”
Section: Compositesmentioning
confidence: 68%
See 1 more Smart Citation
“…However, profiling a concave in the plate and directing it with its front face to the sound wave causes an increase in sound absorption, Figure 11. Taking into account the published results of previous studies [21], which indicated the validity of the use of convexity on the back of the composite plate, which was confirmed in Figure 12, the absorption of the plate with concavity was measured comparatively. The results showed that convexity on the plate is more advantageous than concavity, Figures 11 and 12.…”
Section: Compositesmentioning
confidence: 68%
“…The microscopic structure and surface morphology of natural fibers such as flax, bamboo, kenaf, kapok, coir, cotton, broom, giant reeds, cane, coconut, hemp, etc. are conducive to sound absorption [18][19][20][21][22]. Natural fibers, due to their unique hollow and multi scale structures, show better sound absorption compared to high-modulus fibers such as glass or carbon, especially at frequencies above 1000 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…This work reports the results of experimental measurements of the sound absorption coefficient of ceramic materials using the principle of acoustic resonators. Subsequently, the values obtained from the measurements were used to train a simulation model of the acoustic behavior of the analyzed material based on artificial neural networks [45][46][47][48][49]. The normal incidence absorption coefficient was measured with the Kundt tube, and as expected, with increasing sample thickness, the peak of the bell curve shifts to lower frequencies.…”
Section: Discussionmentioning
confidence: 94%
“…In the images, the low-level features are, for example, the edges or the blobs that are reworked to form high-level features, which, once passed to the last layers of the network, will be able to create, for example, the outlines of houses, dogs, cats, or whatever was present in the original image [151,152]. CNNs process maps of traits where each element corresponds to pixels in the original image.…”
Section: Convolutional Neural Network For Time Series Datamentioning
confidence: 99%